Measuring Sovereign Contagion in Europe - Massimiliano Caporin; Loriana Pelizzon; Francesco Ravazzolo; Roberto Rigobon (Norges Bank, 2012)
This paper analyzes the sovereign risk contagion using CDS spreads for the major euro area countries. Using several econometric approaches (non linear regression, quantile regression and Bayesian quantile with heteroskedasticity) we show that propagation of shocks in Europe's CDS's has been remarkably constant even though in a significant part of the sample periphery countries have been extremely affected by their sovereign debt and fiscal situations. Thus, the integration among the different countries is stable, and the risk spillover among countries is not a effected by the size of the shock.
hdl:11250/2496834
Keywords: E58; F34; F36; G12; G15; 330; sovereign risk; contagion